ANALYSIS OF PERLOCUTIONARY SPEECH ACT IN PRESIDENT BIDEN’S REMARKS ON CONFLICT BETWEEN ISRAEL AND PALESTINE - Ferdin Tri Wahyuda; Siti Aisyah; Esther Hesturini (IKIP Siliwangi, 2024)
The perlocutionary speech acts are an important part of speech acts to find out the response of the effect given by the communicator.The purpose of this study was to identify the types of perlocutionary speech acts and the dominant type of perlocutionary speech acts in President Joe Biden's remarks when talking about terrorist attacks between Israel and Palestine. This research was designed using a qualitative approach by analyzing through three stages, namely data reduction, data display, and drawing conclusions. The results showed that Joe Biden's remarks contained all types of perlocutionary speech acts such as expressive, directive, representative, declarative and commissive with 51 data found. Joe Biden's remarks included 7 expressive acts, 6 directive acts, 5 representative acts, 11 declarative acts, and 6 commissive acts, with declarative acts being the most dominant at 11 instances.